2014
DOI: 10.4103/2152-7806.130314
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an intraoperative ultrasound training model based on a cadaveric sheep brain

Abstract: Background:The present study evaluates the effectiveness of an ultrasound (US) practice course based on a sheep brain cadaver. Neurosurgical education is considerably restrained following patient safety objections and work time restrictions. It is therefore of vital importance to offer residents an opportunity to practice certain US techniques in a controlled environment without ethical or legal restrictions. We developed an US training model based on a sheep brain cadaver in order to demonstrate the feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…To aid certain approaches to such a pathology, intraoperative ultrasound is frequently used to assess the position of the tumour. Training in this regard has been explored by Vavruska et al [18], who evaluated the sheep brain with a transducer and identified similar structures to the human brain.…”
Section: Ovine Modelsmentioning
confidence: 99%
“…To aid certain approaches to such a pathology, intraoperative ultrasound is frequently used to assess the position of the tumour. Training in this regard has been explored by Vavruska et al [18], who evaluated the sheep brain with a transducer and identified similar structures to the human brain.…”
Section: Ovine Modelsmentioning
confidence: 99%
“…In contrast, excessive prolongation of surgical time during intraoperative training can lead to increased intraoperative morbidity. These observations are consistent with previous reports from a German group that proposed to train neurosurgeons with sonography using cadaveric sheep brains (Vavruska et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent IOUS simulation methods e.g. “virtual probes” ( 82 ) or IOUS-simulation smartphone applications ( 82 ), and practice on phantom ( 83 ) or animal ( 84 ) models under supervision of expert sonographers are recommended in order to refine scanning and surgical techniques ( 1 ). As showed recently by group of DiMeco, current high-end 2D IOUS systems integrated with neuronavigation may be in experienced hands of a significant benefit in terms of both extent of brain tumor resections and neurological outcomes ( 85 ).…”
Section: Future Perspectivesmentioning
confidence: 99%